Effects of Dioscorea oppositifolia L. on growth performance, biochemical indicators, immunity, and intestinal health of weaned piglets - Pan, Xiang-Yi; Qiu, Zheng-Ying; Liu, Chen; Wang, Chuan; Wang, Xiaowu; Huang, Li-Na; Li, Si-Fan; Shi, Xiong-Wei; Ge, Shao-Guang; Xin, Rui-Hua (Frontiers in Veterinary Science, 2025)
IntroductionWeaning stress syndrome in piglets seriously endangers the healthy development of the breeding industry. Dioscorea oppositifolia L. (Chinese yam, YAM) has activities such as boosting immunity and regulating gastrointestinal function. In order to explore the potential efficacy of YAM on weaned piglets, this study aimed to investigate the effects of growth performance, immune function, intestinal health and intestinal flora composition of weaned piglets.MethodsForty-eight 28-day-old weaned piglets were randomly divided into a control group, YAML group and YAMH group, with 0, 1 and 2% YAM added to the basal diet, respectively. During the experiment, the piglets’ feed intake was recorded, and blood and fecal samples were collected. After the feeding period, intestinal tissue samples and colon content samples were collected for testing.ResultsThe results showed that adding YAM to the diet can lower the incidence of diarrhea in weaned piglets, improve growth performance and nutrient digestibility, and reduce serum enzyme activity alanine aminotransferase (ALT), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C); in addition, YAM can also increase serum immunoglobulins (Ig) and antibody titers, regulate the level of inflammatory factors, and promote the expression of secretory immunoglobulin A (SIgA) protein in the intestine. Furthermore, supplementation with YAM can increase the villus height (VH), the ratio of villus height to crypt depth (V/C), and the expression of Tight junctions (TJs), and also has a positive regulatory effect on the intestinal flora.DiscussionIn summary, YAM alleviates weaning stress syndrome in piglets by promoting growth performance, improving immune function and disease resistance, improving intestinal morphology and mucosal immunity, and regulating the intestinal microbial composition of piglets. This provides a theoretical basis for the development and application of YAM as a new plant-derived feed additive.